Estimates for Distributions of Suprema of Spherical Random Fields - Sakhno, Lyudmyla (Statistics, Optimization & Information Computing, 2022)
Bounds for distributions of suprema of φ-sub-Gaussian random fields defined over the N-dimensional unit sphere are stated. Applications of the results to the spherical fractional Brownian motion, isotropic Gaussian fields and some other models are presented.